1983
DOI: 10.5636/jgg.35.119
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent source modeling of the core magnetic field using magsat data.

Abstract: An iterative least squares estimation algorithm with the capability for including a priori statistical information has been implemented to recover multiple magnetic dipole models of the Earth's main magnetic field. The dipoles are fixed to a specified radius at or below the core-mantle boundary and centered on equal area blocks. The algorithm can solve for dipole magnitudes only (fixed orientations), or allow full freedom of orientation and solve for vector components. First-order external field parameters can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…In addition to the field generated deep within Earth, induced and remanent magnetization in the crust can be modeled with another set of dipoles, scattered about a sphere of radius 1.0 R e to approximate sources in the crust (Mayhew and Estes, 1983). Earth's field has been approximated by adding one or more smaller dipoles to a 'main dipole' and treating the field as a summation over distinct sources; this provides a simple means of introducing an anomaly, or departure from dipole geometry.…”
Section: The Offset Tilted Dipolementioning
confidence: 99%
“…In addition to the field generated deep within Earth, induced and remanent magnetization in the crust can be modeled with another set of dipoles, scattered about a sphere of radius 1.0 R e to approximate sources in the crust (Mayhew and Estes, 1983). Earth's field has been approximated by adding one or more smaller dipoles to a 'main dipole' and treating the field as a summation over distinct sources; this provides a simple means of introducing an anomaly, or departure from dipole geometry.…”
Section: The Offset Tilted Dipolementioning
confidence: 99%
“…The Earth's field has been approximated by an ensemble of many dipoles located on the surface of a sphere of radius 0.5R e , the fluid core radius. In addition to the field generated deep within Earth, induced and remanent magnetizations in the crust can be modeled with another set of dipoles, scattered about a sphere of radius 1.0R e to approximate sources in the crust (Mayhew and Estes, 1983). A similar approach has been taken to model the crustal magnetic field of Mars (Purucker et al, 2000).…”
Section: The Offset Tilted Dipolementioning
confidence: 99%
“…They used fewer dipoles than MAYHEW and ESTES (1983), but they adjusted the magnetic moment, colatitude, longitude, and distance from the center of the Earth for each dipole using a non-linear least-squares method. To simplify the procedure, a common radius was used for all of the dipoles.…”
Section: R Alldredgementioning
confidence: 99%
“…MAYHEW and ESTES (1983) used dipoles fixed to a specified radius at or below the core-mantle boundary centered on equal area blocks. They found that a model consisting of 93 dipoles arranged 21 degrees apart was comparable inaccuracy to the standard spherical harmonic approach.…”
Section: R Alldredgementioning
confidence: 99%